Kedudukan Wali dalam Perkawinan dan Konsekuensi Hukumnya (Studi Kasus di Desa Hiang Tinggi Kerinci) : The Position of the Guardian in a Marriage and Its Legal Consequences (Case Study in Hiang Tinggi Kerinci Village) - Ayu Lestari, Risna; Darlius, Darlius (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This research aims to reveal the reasons why nasab guardians do not become guardians in marriages as well as the reasons why mosque administrators become substitute guardians and the legal consequences of wrongly using guardians in marriages. This research method is qualitative with a case study approach. Primary data was obtained from traditional leaders, administrators, KUA officials, and nasab guardians. Data was collected through interviews and direct observation, then the collected data was analyzed using descriptive techniques. Based on the research results, the factors that cause religious guardians to be unwilling to become guardians are old age and health, worship, distance, lack of self-confidence, and the duties of mosque administrators. The reasons for the mosque administrator to become a substitute guardian; First, customary provisions and agreements. Second, there is a lack of socialization and cooperation between the village government, traditional leaders and the KUA regarding marriage law. The legal consequences of marriage include fasakh, namely a marriage that does not meet the requirements resulting in fasakh marriage, this is based on law no. 16 of 2019 amendments to law no. 1 of 1974 articles 22, 26 paragraphs 1, 27 paragraphs 1 and 2, and based on KHI article 71 letter e and the provisions of fiqh. The status of the nasab guardian who was replaced by the mosque administrator due to ungodly factors is that his marriage position is valid. However, if the guardian of the nasab had not expired and was replaced by the mosque administrator, the marriage was annulled so the marriage contract had to be repeated.